Teacher Communication Effectiveness in the Learning Process - Ribut Priadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
There are many aspects and aspects that can become the standard for the success or failure of an educational process. This aspect is usually present in the teacher as mentor, teacher and also on the side of students. One aspect that can be a barrier to the success of students in absorbing subjects from the teacher is the factor of communication that is not working effectively. Communication is very important considering that the educational process is currently directed into a room filled by teachers and students. In such conditions a two-way communication pattern is required, in order to create optimal interaction in each face-to-face between teachers and students, so that educational goals can be achieved. This paper will discuss the significance of teacher communication and its effect on student interest in learning.